ARTIFICIAL INTELLIGENCE IN MEDICINE - F.S. Nabiyeva; S.S. Umarova; S.I. Umirkulova (Journal of new century innovations, 2023)
Annotation: the article analyzes the influence of artificial intelligence and its introduction into medicine. We study the history of the emergence of artificial intelligence from the beginning of the experiments of the 50s. Describes the developed products from popular companies. Such as: Ada, Sense.ly, QTrobot, IBM Watson. The article shows how these products help doctors and patients in difficult situations, what actions the program produces when used. With the help of such products, the time and technical costs of obtaining results are reduced.